EFFECT OF CULTIVARIS, BUDDING DATES, KINETIN, AND THEIR INTERACTION ON THE BUDDING AND VEGETATIVE GROWTH CHARACTERISTICS OF PISTACHIO TRANSPLANTS “Pistacia vera L.” - IBRAHIM , NAWZAD JEMIL; MAYI, AZAD AHMED (Journal of Duhok University, 2023)
The experiment was conducted during the growing season (2021) at a private orchard in Bani village, Dohuk City, Kurdistan Region-Iraq. The research aimed to produce transplants of pistachio with certified cultivars for commercial marketing purposes, using the T-budding method on one-year-old seedling pistachio rootstocks. The study investigated the effect of three cultivars (Abas-Ali, Kale-gnocchi, and Siirt), three budding dates (mid-June, mid-August, and mid-September), three Kinetin concentrations (0, 5, and 10 mg/L) and their interaction. The finding results indicated that the Siirt cultivar had the highest budding success percentage (59.1%) and total chlorophyll content (54.2 SPAD) compared to the other cultivars. However, the mid-June budding date showed the highest success percentage of budding (56.4%) and leaf number per transplant (39) compared to the other budding dates. Additionally, the third concentration of Kinetin (10 mg/L) significantly increased the budding percentage (57.6%), leaf area (21.9 cm²), and total chlorophyll (55.6 SPAD). And, the interaction between the Siirt cultivar, the mid-June date, and the third concentration of Kinetin resulted in the highest budding success percentage (73.3%). These findings suggest that the selection of appropriate cultivars, budding dates, and appropriate concentration of Kinetin can significantly impact the success percentage and quality of pistachio transplant production in the nursery for commercial marketing purposes